Green tea drinking, high tea temperature and esophageal cancer in high‐ and low‐risk areas of Jiangsu Province, China: A population‐based case–control study - Wu, Ming; Liu, Ai‐Min; Kampman, Ellen; Zhang, Zuo‐Feng; van't Veer, Pieter; Wu, De‐Lin; Wang, Pei‐Hua; Yang, Jie; Qin, Yu; Mu, Li‐Na; Kok, Frans J.; Zhao, Jin‐Kou (International journal of cancer, 2009)
Epidemiological studies suggested drinking green tea is inversely associated with esophageal cancer but results remain inconclusive. Moreover, inconsistent observations found high temperature drinks are associated with esophageal cancer. A population‐based case–control study was conducted in a high‐risk area (Dafeng) and a low‐risk area (Ganyu) of esophageal cancer in Jiangsu province China from 2003 to 2007. It aimed to explore green tea drinking and tea temperature with the risk of esophageal cancer, and to compare the difference between different risk regions. Using identical protocols, 1,520 cases and 3,879 healthy controls were recruited as study subjects in 2 regions. Detailed information was collected to assess green tea drinking habits. Unconditional logistic regression was used to obtain OR and 95% CI. Results showed that ever drinking green tea elevated OR in both counties (Dafeng OR = 1.2, 95% CI = 0.9–1.5; Ganyu: OR = 1.9, 95% CI = 1.4–2.4). Drinking tea at high temperature was found to increase cancer risk in both areas (Dafeng: OR = 1.9, 95% CI = 1.2–2.9; Ganyu OR = 3.1 95% CI = 2.2–4.3). However, after further adjustment for tea temperature, ever drinking tea was not related to cancer in either county (Dafeng: OR = 1.0, 95% CI = 0.7–1.3; Ganyu: OR = 1.3, 95% CI = 0.9–1.7). For dose‐response relationships, we observed positive relationship with monthly consumption of tea (p for trend = 0.067) and tea concentration (p for trend = 0.006) after further adjustment for tea temperature. In conclusion, green tea drinking was not inversely associated with esophageal cancer in this study. However, drinking tea at high temperatures significantly increased esophageal cancer risk. There was no obvious difference of green tea drinking between low‐ and high‐risk areas. © 2008 Wiley‐Liss, Inc.